Shifts in precipitation regimes exacerbate global inequality in grassland nitrogen cycles - Miao Zheng; Jinglan Cui; Xiaoxi Wang; Xiuming Zhang; Zhongrui Xie; Ruoxi Zhang; Xinpeng Xu; Baojing Gu (Nature Communications)
Abstract Grasslands, the Earth’s largest terrestrial ecosystem, provide crucial ecosystem services through biogeochemical cycles. However, these cycles are disrupted by climate change, particularly precipitation changes, limiting grassland productivity. By synthesizing 2944 experimental observations and integrating multiple models, here we show that under the middle-of-the-road scenario, global nitrogen input, harvest, and surplus from grasslands are projected to increase by 10, 7, and 3 million tonnes per year (Tg yr−1), respectively. Substantial regional inequalities are expected. Regions with increased precipitation (mainly the United States, northern Australia, much of Asia) may see a 16 Tg yr−1 increase in nitrogen harvest. Conversely, regions with decreased precipitation (mainly Sub-Saharan Africa, Latin America, Southeast Asia) will see a 9 Tg yr−1 reduction. Timely adaptation measures could reduce nitrogen input and surplus by 12 and 22 Tg yr−1, respectively, while boosting nitrogen harvest by 10 Tg yr−1, potentially averting losses of 238 billion USD by 2050.